Productivity of Contingency in the Popular Economies of the Global South. A Dialogue with AbdouMaliq Simone. - Cristina Cielo (Íconos)
Productivity of Contingency in the Popular Economies of the Global South. A Dialogue with AbdouMaliq Simone